Decoding the role of the cerebellum in the early stages of reading acquisition. (August 2021) - Li, Hehui; Kepinska, Olga; Caballero, Jocelyn N.; Zekelman, Leo; Marks, Rebecca A.; Uchikoshi, Yuuko; Kovelman, Ioulia; Hoeft, Fumiko
Abstract: Numerous studies have consistently reported functional activation of the cerebellum during reading tasks, especially in the right cerebellar hemisphere. However, it remains unclear whether this region is also involved in reading during the earliest stages of reading acquisition. Here, we investigated whether and how the cerebellum contributes to reading acquisition. We tested 80 5-6-year-old kindergarteners, who performed a visual word matching task during which functional MRI (fMRI) data were collected. We found that bilateral cerebellar hemispheres were significantly activated during visual word processing. Moreover, activation of left cerebellar lobule VII extending to lobule VIII negatively and significantly correlated with current reading ability, whereas activation of right cerebellar lobule VII extending to lobule VIII significantly and positively correlated with future reading ability. Functional decoding via functional connectivity patterns further revealed that left and right cerebellar lobules connected with different cerebral cortex regions. Our results suggest a division of labor between the left and right cerebellar lobules in beginning readers.